Gas Exchange and Productivity in Temperate and Droughty Years of Four Eastern, Elite Loblolly Pine Genotypes Grown in the Western Gulf Region - Michael A. Blazier; Michael C. Tyree; Mary Anne Sword Sayer; Dipesh KC; Wilson G. Hood; Bradley S. Osbon (International Journal of Agronomy)
Loblolly pine plantations in the western portion of the species’ range are sometimes planted with genotypes from the eastern portion of its range to improve plantation productivity. Advances in loblolly pine breeding have led to the development of clonally propagated genotypes with higher potential growth rates and better form than more commonly planted half-sib genotypes. At a site in the western portion of the loblolly pine range, four genotypes from the eastern portion of the loblolly pine range were established. Two genotypes (HS756 and HS8103) were half-sib, and two genotypes (V9 and V93) were varieties. The V93 genotype was propagated from the HS756 genotype. The objective of this study was to determine the effects of genotype on seasonal trends in gas exchange parameters at the leaf and crown levels, growth, and biomass allocation patterns. During the two-year study, one year had precipitation and temperature trends similar to the long-term average and one year had extreme drought, with record heat. The HS756, V9, and V93 genotypes had the highest height growth throughout the study. The V93 genotype was sensitive to the drought; its leaf- and crown-level Asat and gs, declined during the drought more markedly than those of the other genotypes. Although its Asat and gs were affected by drought, height growth productivity of V93 may have been sustained during the drought by its biomass partitioning pattern of allocating higher proportions of its root biomass to small and fine roots and its aboveground biomass to foliage. These results suggest that a variety such as V93 could be more susceptible to changes in C fixation and water uptake with recurrent drought.